Fuel Cells: Interlocking Membrane/Catalyst Layer Interface for High Mechanical Robustness of Hydrocarbon‐Membrane‐Based Polymer Electrolyte Membrane Fuel Cells (Adv. Mater. 19/2015). (13th May 2015) - Oh, Keun‐Hwan; Kang, Hong Suk; Choo, Min‐Ju; Jang, Duk‐Hun; Lee, Dongyoung; Lee, Dai Gil; Kim, Tae‐Ho; Hong, Young Taik; Park, Jung‐Ki; Kim, Hee‐Tak
Abstract : A new solution for enhancing interfacial adhesion between the hydrocarbon (HC) membrane and a perfluorinated catalyst layer (CL) in polymer electrolyte fuel cells (PEMFCs) is successfully demonstrated by J.‐K. Park, H.‐T. Kim, and co‐workers on page 2974. This is realized by the intrusion of micrometer‐sized pillars fabricated on the HC membrane into the perfluorinated CL, forming an interlocking interface, like Lego blocks. Owing to a higher expansion with hydration for the HC membrane than for the perfluorinated CL, a strong normal force occurs at the interface of the pillars and the holes, resulting in an eight‐fold increase of the interfacial bonding strength.